Differentiation-inducing ability of sophorolipids of oleic and linoleic acids using a glioma cell line - Joshi-Navare, Kasturi; Shiras, Anjali; Prabhune, Asmita (Biotechnology Journal, 2011)
Sophorolipids are biosurfactants produced by non-pathogenic yeasts. They show structural similarity with the membrane components of mammalian cells, i.e., glycosphingolipids and gangliosides, which are involved in processes such as signaling, oncogenesis, and differentiation. Sophorolipids have been reported to induce differentiation in several leukemic cell lines, cell death via apoptosis in a human liver cancer cell line, and necrosis in a pancreatic adenocarcinoma cell line. Here we report, for the first time, the effects of precursor fatty acids and sophorolipids of oleic and linoleic acids in pure acidic and crude forms on LN-229, a glioma cell line. In response to different sophorolipid forms, various morphological changes were observed, such as formation of long thread-like extensions arising from the ends of the cells, cell alignment, cell elongation and bundle formation in a dose-dependent manner. In this study we present the morphological evidence of the potential of sophorolipids as differentiation inducers.
Keywords: Differentiation; Glioma; LN-229; Sophorolipid

Biosurfactant-sophorolipid acts in synergy with antibiotics to enhance their efficiency - Joshi-Navare, Kasturi; Prabhune, Asmita (Biomed Research International, 2013)
Sophorolipids (SLs), biosurfactants with antimicrobial properties, have been tried to address the problem of antibiotic resistance. The synergistic action of SL and antibiotics was checked using standard microdilution and spread plate methods. With Staphylococcus aureus, SL-tetracycline combination achieved total inhibition before 4 h of exposure while tetracycline alone couldnot achieve total inhibition till the end of 6 h. The inhibition caused by exposure of bacterium to SL-tetracycline mixture was similar to 25% more as compared to SL alone. In spite of known robustness of gram-negative bacteria, SL-cefaclor mixture proved to be efficient against Escherichia coli which showed similar to 48% more inhibition within 2 h of exposure as compared to cefaclor alone. Scanning electron microscopy of the cells treated with mixture revealed bacterial cell membrane damage and pore formation. Moreover, SLs being a type of asymmetric bola, they are expected to form self-assemblies with unique functionality. This led to the speculation that SLs being amphiphilic in nature can span through the structurally alike cell membrane and facilitate the entry of drug molecules.

Crystalline xylitol production by a novel yeast, pichia caribbica (HQ222812), and its application for quorum sensing inhibition in gram-negative marker strain chromobacterium violaceum CV026 - Mukherji, Ruchira; Joshi-Navare, Kasturi; Prabhune, Asmita (Applied Biochemistry and Biotechnology, 2013)
Xylitol, a sugar alcohol, is fast gaining ground over other artificial sugar substitutes owing to its advantageous properties. Xylitol is a safer alternative for diabetics because of insulin-independent metabolism. It has beneficial properties suitable to form an important part of odontological formulations. Conventional commercial production of xylitol involves harsh chemical method operating at high temperature and pressure. Thus, microbial production of xylitol is preferred over chemical method, and yeasts have been extensively exploited for this purpose. In the present manuscript, quantitative production of xylitol from d-xylose with the yield of 0.852 gm/gm and volumetric productivity of 1.83 gm/l/h in crystalline form, using novel yeast Pichia caribbica is reported. Also, a mild, safe procedure for product extraction is described. The ability of xylitol to act as a quorum sensing antagonist in gram-negative marker strain Chromobacterium violaceum CV026 has been demonstrated for the first time.
Keywords: Crystallization; CV026; Pichia caribbica; Quorum sensing antagonist; xylitol

Fluorescent sophorolipid molecular assembly and its magnetic nanoparticle loading: a pulsed laser process - Singh, Pradeep Kumar; Mukherji, Ruchira; Joshi-Navare, Kasturi; Banerjee, Abhik; Gokhale, Rohan; Nagane, Satyawan; Prabhune, Asmita; Ogale, Satishchandra (Green Chemistry, 2013)
We report realization of strong green fluorescence in a fully biocompatible highly spherical mesoscale molecular assembly of sophorolipid created by pulsed UV laser processing of a water-based dispersion of sophorolipid. Remarkably, the said fluorescence is totally absent in the original molecule of sophorolipid and is thus the property of the pulsed laser induced modifications in the molecule and the assembly. We have separately examined the consequences of laser irradiation for glucose and oleic acid components which form the sophorolipid. This fluorescence character appears to be driven by the oleic acid component while the assembly process is assisted by the glucose component. Importantly the laser synthesized mesostructures can be easily redispersed in an aqueous medium after being dried and can also be loaded with magnetic nanoparticles (magnetite) for inducing the hyperthermia effect.

New yeast isolate Pichia caribbica synthesizes xylolipid biosurfactant with enhanced functionality - Joshi-Navare, Kasturi; Singh, Pradeep Kumar; Prabhune, Asmita (European Journal of Lipid Science and Technology, 2014)
Sophorolipids (SL) belong to a class of glycolipidic biosurfactants suitable for a wide range of applications. The structural diversity in SL gives rise to variation in physicochemical and biological properties. To achieve the less explored head group diversity in sophorolipid structure, a new xylose fermenting yeast Pichia caribbica has been employed for biosurfactant production. The media and fermentation parameters have been optimized to achieve maximum yield of 7.48 g/L. The physicochemical properties of the xylolipid biosurfactant have been assessed. It reduced the surface tension of distilled water from 70 to 35.9 mN/m with the low critical micellar concentration (CMC) 1.0 mg/L as compared to typical SL (reported CMC range 40-100 mg/L). Structural characterization was done using FTIR and HR-MS to identify the structure. 17-L-[(beta-D-xylopyranosyl)-oxy]-Delta 9-heptadecanoic acid correlated to m/z 415 majorly constituted the product. Control experiment was performed in which glucose was provided as the hydrophilic carbon. This product was also subjected to HR-MS analysis to determine its chemical nature and found to be different from xylolipid. Presence of xylose as head group was anticipated to give altered physicochemical and biological activities and indeed a low CMC value and better inhibitory action was demonstrated against Staphylococcus aureus. Practical applications: Sophorolipids produced by microbial sources have several advantageous properties over commercial petroleum-based surfactants including biodegradability, environmentally friendly nature, and low toxicity. Here, we have attempted to modify the hydrophilic head group by incorporating xylose in place of glucose. This molecule will also behave differently in response to different stimuli. Stimuli-responsive surfactants are a class of compounds with applications in stabilization of emulsions, suspensions or foams, drug encapsulation and delivery, hard-surface cleaning, personal care applications.
Keywords: Antibacterial action; Critical micelle concentration; Pichia caribbica; Sophorolipid; Xylolipid